Optimisation de l'énergie et la prédiction de dispersion pour la transmission RZ non linéaire - SALMI, Hiba; BELAMRI, Anwar Essadat; Enca/ BOURAS, Mounir (University of M'sila, 2023)
Most of the fibers installed are standard single-mode fibers. To achieve a good level of bit error rate (BER) as well as to allow greater spacing between repeaters and a greater signal to noise ratio (SNR) in this type of fiber, it is very important to take into account the influence of group speed. Increasing the capacity of optical systems may require either increasing the bit rate, using WDM, or both. At high bit rates, the modulation format, the type of dispersion compensation scheme and the channel power become important elements for the optimal system design. In particular, it has been shown numerically and experimentally that the conventional non-return-to-zero (NRZ) modulation format is superior to return-to-zero (RZ) modulation in the case of large WDM systems, because the modulation RZ causes a significant loss of time. Penalty for closing eyes near end canals. Our goal is to study these two types of RZ and NRZ coding to compare the penalties for closing eyes.
Keywords: RZ coding, NRZ coding, Chromatic dispersion, Wavelength.